Developmental paleobiology of the vertebrate skeleton. (July 2014) - Rücklin, Martin; Donoghue, Philip C. J.; Cunningham, John A.; Marone, Federica; Stampanoni, Marco
Abstract : Studies of the development of organisms can reveal crucial information on homology of structures. Developmental data are not peculiar to living organisms, and they are routinely preserved in the mineralized tissues that comprise the vertebrate skeleton, allowing us to obtain direct insight into the developmental evolution of this most formative of vertebrate innovations. The pattern of developmental processes is recorded in fossils as successive stages inferred from the gross morphology of multiple specimens and, more reliably and routinely, through the ontogenetic stages of development seen in the skeletal histology of individuals. Traditional techniques are destructive and restricted to a 2-D plane with the third dimension inferred. Effective non-invasive methods of visualizing paleohistology to reconstruct developmental stages of the skeleton are necessary. In a brief survey of paleohistological techniques we discuss the pros and cons of these methods. The use of tomographic methods to reconstruct development of organs is exemplified by the study of the placoderm dentition. Testing evidence for the presence of teeth in placoderms, the first jawed vertebrates, we compare the methods that have been used. These include inferring development from morphology, and using serial sectioning, microCT or synchrotron X-ray tomographic microscopy (SRXTM), to reconstruct growth stages and directions of growth. The ensuing developmental interpretations are biased by the methods and degree of inference. The most direct and reliable method is using SRXTM data to trace sclerochronology. The resulting developmental data can be used to resolve homology and test hypotheses on the origin of evolutionary novelties.